Simplify 5 + 2{x - 4[3x + 7(2 - x)]}.

Question

Asked 1/29/2013 8:52:47 AM

Updated 6/8/2014 11:53:38 AM

2 Answers/Comments

s

twistedechoes|Points 46|

andrewpallarca|Points 18976|

yestfl|Points 1444|

ronaldkervingo|Points 104|

vchutkan|Points 5734|

rachell028|Points 992|

rachell028|Points 992|

utahclock|Points 127|

OxTornado007|Points 6639|

Elle124|Points 298|

OxTornado007|Points 6639|

utahclock|Points 127|

utahclock|Points 127|

kserrano|Points 100|

Elle124|Points 298|

caligun|Points 1291|

jeifunk|Points 8521|

Elle124|Points 298|

migzptz|Points 7342|

jeifunk|Points 8521|

Elle124|Points 298|

andrewpallarca|Points 18976|

stan_r|Points 1382|

LoveSolo|Points 80|

eturker|Points 2852|

Expert answered|jeifunk|Points 8521|

Question

Asked 1/29/2013 8:52:47 AM

Updated 6/8/2014 11:53:38 AM

2 Answers/Comments

Rating

3

5 + 2{x - 4[3x + 7(2 - x)]}

= 5 + 2{x - 4[3x + 14 - 7x]}

= 5 + 2{x - 4[-4x + 14]}

= 5 + 2{x + 16x - 56}

= 5 + 2{17x - 56}

= 5 + 34x - 112

= 34x - 107

= 5 + 2{x - 4[3x + 14 - 7x]}

= 5 + 2{x - 4[-4x + 14]}

= 5 + 2{x + 16x - 56}

= 5 + 2{17x - 56}

= 5 + 34x - 112

= 34x - 107

Added 6/8/2014 11:53:03 AM

This answer has been confirmed as correct and helpful.

3

(7q - 5)(7q + 5)

= 49q^2 + 35q - 35q - 25

= 49q^2 - 25

= 49q^2 + 35q - 35q - 25

= 49q^2 - 25

Added 6/8/2014 11:53:38 AM

This answer has been confirmed as correct and helpful.

Select the correct product.
(2x + 9)(x + 1)
2x2+ 11x+ 9
3x2+ 11x+ 9
2x2- 7x+ 9
2x2+ 11x+ 10 User: (2x + 9)(x + 1) **Weegy:** If h(x) = 5 for the function h(x) = 2x + 1, then x equals 2. h(2) = 2(2) + 1 = 5. The answer is 2.
**User:** 36m5n5 ÷ (12m3)
**Weegy:** 36m5n5 ? (12m3) = 3m2n5 **User:** 7 - 3[(n3 + 8n) ÷ (-n) + 9n2] **Weegy:** 3-3 = 0 (More)

Question

Updated 5/29/2014 9:44:25 AM

2 Answers/Comments

(2x + 9)(x + 1)

= 2x^2 + 2x + 9x + 9

= 2x^2 + 11x + 9

= 2x^2 + 2x + 9x + 9

= 2x^2 + 11x + 9

Added 5/29/2014 9:42:31 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/29/2014 9:55:21 AM]

Factor 3y2 - 4y.
y(4 - 3y)
y(3y - 4)
y(4y - 3) User: Factor 48m - 80n.
16mn(3m - 5n)
16(5n - 3m)
16(3m - 5n) **Weegy:** Answer is C) 16(3m - 5n). Solution 1. Find the lowest common denominator for both numerical coefficient 48= 2.2.2.2.3 80=2.2.2.2. 5 LCD= 2.2.2.2 LCD = 16 2. Perform the operation: 48m - 80n divide both by 16 *48m/16 = 3m *-80/16 = -5n 3. answer= 16(3m - 5n) **User:** Factor x4y2 + x3y3.
x3y2(x + 1)
x2y2(x + y)
x3y2(x + y) **Weegy:** The answer is 3x^4y^5.
**User:** -24a3b3c3 - 84a4b2c factored equals -12a3b2c(2bc2 + 7a).
True
False **Weegy:** True **User:** Factor 10x3 + 8x2 - 6x.
2x(5x + 4x - 3)
2x(5x + 4x2- 3)
2x(5x2+ 4x - 3) **Weegy:** 10x^3 + 8x^2 - 6x factored would be (c)2x(5x^2+ 4x - 3) **User:** Factor 2a5b + 2a4b2 + 2a3b3.
2a2b(a2+ ab2+ ab)
2a3b(a2+ ab + b2)
2ab3(a3+ ab + b2) **Weegy:** 2a5b + 2a4b2 + 2a3b3, factors are 2a3b(a2+ ab + b2) (More)

Question

Expert Answered

Updated 6/10/2014 11:32:40 PM

1 Answer/Comment

31,870,193

questions answered

There are no comments.